Characterization of sunburn damage to apple fruits and leaves - Racskó, J.; Szabó, T.; Nyéki, J.; Soltész, M.; Nagy, P. T. (International Journal of Horticultural Science, 2010)
The specific conditions of the formation of three different types of sunburn (sunburn browning, sunburn necrosis, and photooxidative sunburn) have been recently characterized on apple fruit. However, no information is still available on leaf damage. Therefore, the aims of this study were i) to extend the knowledge on fruit damage, ii) characterize leaf damage and iii) find relationship between fruit and leaf damage. The observations were made on 586 apple accessions in a gene bank orchard located in Hungary. The incidence of the three different types of fruit symptoms were recorded and based on the visual symptoms, two different types of leaf sunburn (sunburn yellowing and sunburn necrosis) were characterized. The most frequent type of fruit sunburn observed was sunburn browning. Photooxidative sunburn was found for less number of accessions, and only some accessions were affected by sunburn necrosis. Fruit were far more susceptible than leaves; (>60%) of the examined accessions were affected by fruit damage and (